PEELING OF THE INTERNAL LIMITING MEMBRANE WITH FOVEAL SPARING FOR TREATMENT OF DEGENERATIVE LAMELLAR MACULAR HOLE. Issue 6 (June 2020) - Morescalchi, Francesco; Russo, Andrea; Gambicorti, Elena; Cancarini, Anna; Scaroni, Nicolò; Bahja, Hassan; Costagliola, Ciro; Semeraro, Francesco
Abstract : Purpose: To compare the functional and anatomical results of fovea-sparing internal limiting membrane peeling during vitrectomy with those of observation for degenerative lamellar macular hole with lamellar hole–associated epiretinal proliferation. Design: A prospective, randomized, comparative pilot study. Methods: Thirty-six eyes were randomized to undergo surgery with foveal internal limiting membrane sparing (Group S) or observation only (Group C). The main outcome measures were foveal retinal sensitivity, visual acuity, and central retinal thickness. Results: After 6 months, a significant difference was found in foveal retinal sensitivity between Group S (12.8 ± 1.7 dB) and Group C (9.39 ± 1.8 dB; P < 0.001). Similarly, best-corrected visual acuity improved in Group S and remained stable in Group C (respectively, 0.17 ± 0.13 and 0.46 ± 0.21 logMAR; P < 0.001). A significant increase in central retinal thickness was observed in Group S, but not in Group C (272 ± 24 vs. 147 ± 20 µ m, P < 0.001). Conclusion: Fovea-sparing internal limiting membrane peeling is a feasible treatment for degenerative lamellar macular hole with lamellar hole–associated epiretinal proliferation, yielding better improvements in best-corrected visual acuity and foveal retinal sensitivity than observation alone. Further studies are needed to optimize this new surgical approach. Abstract : Supplemental Digital Content is Available in the Text.This study compared the functional and anatomical results of fovea-sparing internal limiting membrane peeling during vitrectomy with those of observation for degenerative lamellar macular hole with lamellar hole–associated epiretinal proliferation. Fovea-sparing internal limiting membrane peeling is a feasible treatment, yielding better improvements in best-corrected visual acuity and foveal retinal sensitivity than observation alone.